War Discourse in the Biographical Novels About Artists: Intermedial Aspect - Levytska, Oksana; Mocherniuk, Nataliia (Respectus Philologicus, 2023)
War narrative in the biographical novels about painters has been analysed in their intermedial links with the paintings of said artists. The object of analysis is novels about the Spanish artist Francisco Goya written by Manfred Schneider, Carlos Rojas, and Jacek Dehnel; Ralf Dutli’s novel about Chaim Soutine; and a separate section dedicated to a selection of novels about Ukrainian artists: Ivan Holubkovskyi’s text about Oleksa Novakivskyi, Stanislav Stetsenko’s work about Mykola Hlushchenko, Kateryna Lebedieva’s book about Les Kozlovskyi, Volodymyr Yavorivskyi’s novel about Kateryna Bilokur. At the core of the study is the intermedial methodology based on theory by I. Rajewski, A. Hansen-Löve, S. Macenka, and A. Berger. Different aspects of war discourse in novels and its interaction with the creations of artists have been identified and highlighted, i.e., thematisation of war, description of painting creation, ekphrasis and references to works of art, use of art poetics in a literary text, aesthetics and psychology of creativity stipulated by war.